COVID -19 Lockdown and Effect on Individual Economy in the Lucknow city - Awasthi, Aishwarya; Singh, Shivendra Kumar (Indian Journal of Community Health, 2024)
The COVID-19 pandemic has exhibit deep stress all over the world. Despite recent speculative suggestions of poorer psychological state in all age in India, since the beginning of the pandemic, there are no systematic efforts to help consequences. This research tried to report on the content of effect of lockdown on individual economy in Luck now city, those who could also be notably liable to negative emotions alongside news on the impact of corona virus on their lives. These impacts consecutively related to negative have an effect on. Participants' high worries centred on economy attainments, social and recreational activities, and physical health. A lot of females than males disturbed regarding educational attainment and physical health whereas a lot of males disturbed regarding economical, social and recreational activities. Thus, Indian individuals report important impact of the pandemic on varied aspects of their life and area unit notably disturbed regarding economical and educational attainments, social and recreational activities and physical health. During pandemic and lockdown people lost their jobs, their business were closed, they have had no option for their livelihood They were suffered from more stress. They were panic to thought about how to move their family life. How to secure their family. Thus Pandemics are extremely impactful and endangering the protection and traditional functioning of the community.